A method for testing bentonite composite sand casting

By using bentonite composite sand, combined with kaolin and talc powder, an efficient sand binder formula is formed, which solves the problem of sand bonding, environmental pollution and waste sand reuse during the casting process, and realizes the reusability and resource utilization of molded sand, and meets the requirements of high-strength-rate wet molding technology.

CN115502327BActive Publication Date: 2025-03-25HANGZHOU JIEZHU TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211138072.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-19
Publication Date
2025-03-25
Estimated Expiration
2042-09-19

AI Technical Summary

Technical Problem

During the casting process, existing molded sand has problems such as sand sticking, environmental pollution and waste sand reuse, and the inorganic binder has low strength and poor moisture resistance.

Method used

Using bentonite composite sand, the reusability and resource utilization of the sand are achieved by mixing 75% to 80% bentonite, 10% to 15% kaolin and 5% to 15% talc powder, and adding an appropriate amount of water and quartz sand to form an efficient sand binder formula to achieve the reusability and resource utilization of the sand.

Benefits of technology

It has achieved good film removal performance of molded sand, non-stick sand, low raw material cost, waste sand can be reused, energy-saving and environmentally friendly, and meets the requirements of high-strength-rate wet molding technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115502327B_ABST
    Figure CN115502327B_ABST
Patent Text Reader

Abstract

The present invention provides a method for casting test of bentonite composite sand, the method comprising the steps of: mixing 75% to 80% bentonite, 10% to 15% kaolin, and 5% to 15% talcum powder uniformly to obtain a first mixture by mass fraction; mixing the first mixture with quartz sand at a mass ratio of 1:18 to 22, adding an appropriate amount of water during the mixing process to obtain a second mixture with a humidity of 5% to 10%; pressing the second mixture to obtain a sample of a predetermined shape; detecting the wet compressive strength of the sample, and performing a casting test on the sample that meets the wet compressive strength. The present invention has the advantages of good demolding performance of the prepared molding sand, no sand sticking, low raw material cost, reuse of the generated waste sand, energy saving and environmental protection, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic non-metallic functional materials, and in particular relates to a method for sand casting test using a bentonite composite formulation. Background Art

[0002] The molding sand system is composed of a series of raw materials such as backbone materials, additives, and binders. The performance of molding sand mainly depends on the binder and additives. According to the different types of binders, molding sand can be divided into clay molding sand, inorganic chemical sand, resin sand, etc. There are also some molding sands with organic substances such as vegetable oil or mineral oil as binders. However, organic binders have high environmental hazards and high production costs. Inorganic binders have disadvantages such as low specific strength and poor moisture resistance. On the contrary, clay binders have the advantages of good disintegration, low cost and reusability, and are favored by the majority of foundry industries. Bentonite has good bonding properties, easy demoulding and relatively stable performance under high temperature conditions, so it is often used as a binder for traditional casting in clay wet sand. Coal powder is often added to wet sand to prevent sand from sticking to the surface of the casting, inhibit expansion defects and reduce pores, which can effectively reduce the surface roughness of cast iron parts and improve the quality of castings. However, this type of wet sand has problems such as environmental pollution and difficulty in meeting the requirements of high compaction rate wet mold molding process during production, so it is urgent to develop new coal powder substitute materials. The mechanism of coal powder's function mainly has three points: generating bright carbon, generating reducing atmosphere and coke slag characteristics at high temperature. Therefore, new coal powder substitute materials should have the following characteristics: (1) having high bright carbon generation characteristics; (2) low ash and sulfur content; (3) non-toxic and harmless; (4) cheap and easy to obtain.

[0003] At present, in casting production, castings produced by sand casting account for 90% of the total casting production, and clay sand technology accounts for about 85% of sand casting. Generally speaking, 1 to 1.2 tons of waste sand are generated for every ton of castings produced. Therefore, the recycling of old clay sand is a major problem that needs to be solved in the foundry industry. Summary of the invention

[0004] The purpose of the present invention is to solve at least one of the above-mentioned deficiencies in the prior art. For example, one of the purposes of the present invention is to provide a method for molding sand casting test using bentonite composite agent, which has good molding sand demoulding performance, does not stick to sand, has low raw material cost, can reuse the waste sand produced, and is energy-saving and environmentally friendly.

[0005] In order to achieve the above object, one aspect of the present invention provides a method for sand casting test using bentonite composite formulation, the method comprising the steps of:

[0006] By mass fraction, 75% to 80% of bentonite, 10% to 15% of kaolin, and 5% to 15% of talc are uniformly mixed to obtain a first mixed material;

[0007] The first mixed material and quartz sand are mixed in a mass ratio of 1:18-22, and a proper amount of water is added during the mixing process to obtain a second mixed material with a humidity of 5%-10%;

[0008] Pressing the second mixed material into a sample to obtain a sample of a predetermined shape;

[0009] The wet compressive strength of the samples is tested, and samples that meet the wet compressive strength requirements are subjected to a casting test.

[0010] In an exemplary embodiment of an aspect of the present invention, the bentonite may include:

[0011] By mass percentage, 0% to 60% SiO2, 20% to 30% Al2O3, 10% to 15% Na2O, 1% to 5% MgO and 5% to 10% CaO.

[0012] In an exemplary embodiment of an aspect of the present invention, the kaolin may include:

[0013] By mass percentage, 50% to 55% SiO2, 10% to 15% K20 and 30% to 40% Al203.

[0014] In an exemplary embodiment of an aspect of the present invention, the talc may include:

[0015] By mass percentage, 50% to 60% SiO2, 10% to 15% K20 and 30% to 40% Al203.

[0016] In an exemplary embodiment of an aspect of the present invention, the pressing may include:

[0017] The second mixed material is placed in a mold and pressed into a cylinder with a height of 4.0 cm to 6.0 cm and a diameter of 4.0 cm to 6.0 cm using a hammer press.

[0018] In an exemplary embodiment of an aspect of the present invention, the wet compressive strength may be 30 kPa to 70 kPa.

[0019] In an exemplary embodiment of one aspect of the present invention, the quartz sand may be industrial standard sand, and the particle size may be 50 mesh to 100 mesh or 70 mesh to 140 mesh.

[0020] In an exemplary embodiment of one aspect of the present invention, the particle size of the bentonite, kaolin and talc may be 100-200 meshes.

[0021] In an exemplary embodiment of an aspect of the present invention, the method may further comprise the steps of:

[0022] Before mixing bentonite, kaolin and talc, the bentonite, kaolin and talc are dried respectively so that their respective moisture contents are ≤3%.

[0023] Compared with the prior art, the beneficial effects of the present invention may include at least one of the following:

[0024] (1) The bentonite composite molding sand of the present invention mainly uses bentonite, kaolin and talc as raw materials to produce an efficient molding sand binder formula, thereby achieving the reusability of the molding sand, realizing resource utilization, and reducing environmental pollution;

[0025] (2) The molding sand sample prepared by the present invention has a higher demolding property, and the prepared sample is less likely to be stuck with sand;

[0026] (3) The raw materials used in the present invention have low ash and sulfur content and are non-toxic and harmless; no toxic or harmful gases are generated during the casting process;

[0027] (4) The materials used in the method of the present invention are cheap and readily available, and the market prices of the samples used are relatively low.

[0028] Instruction Manual

[0029] Figure 1 shows an XRD pattern of raw bentonite used in an exemplary embodiment of the present invention;

[0030] Figure 2 shows an XRD pattern of raw kaolin used in an exemplary embodiment of the present invention;

[0031] Figure 3 The XRD pattern of raw talc powder used in an exemplary embodiment of the present invention is shown. DETAILED DESCRIPTION

[0032] Hereinafter, a method for sand casting test using bentonite composite formulation of the present invention will be described in detail in conjunction with exemplary embodiments.

[0033] Figure 1 shows an XRD pattern of raw bentonite used in an exemplary embodiment of the present invention; Figure 2 shows an XRD pattern of raw kaolin used in an exemplary embodiment of the present invention; Figure 3 The XRD pattern of raw talc powder used in an exemplary embodiment of the present invention is shown.

[0034] In a first exemplary embodiment of the present invention, the method of using bentonite composite sand casting test mainly includes the steps of:

[0035] According to the mass fraction, 75% to 80% of bentonite, 10% to 15% of kaolin, and 5% to 15% of talc are uniformly mixed to obtain a first mixed material. The first mixed material is mixed with quartz sand at a mass ratio of 1:18 to 22, and an appropriate amount of water is added during the mixing process to obtain a second mixed material with a humidity of 5% to 10%. Here, the first mixed material is mixed with quartz sand at a mass ratio of 1:20. The second mixed material is pressed to obtain a sample of a predetermined shape.

[0036] The wet compressive strength of the samples is tested, and samples that meet the wet compressive strength requirements are subjected to a casting test.

[0037] In this exemplary embodiment, the main component of the bentonite is montmorillonite, and its chemical composition may include, by mass percentage, 0% to 60% SiO2, 20% to 30% Al2O3, 10% to 15% Na2O, 1% to 5% MgO and 5% to 10% CaO.

[0038] Furthermore, the main component of the kaolin is kaolinite, and its chemical composition may include: by mass percentage, 50% to 55% SiO2, 10% to 15% K20 and 30% to 40% Al203.

[0039] Furthermore, the main component of the talcum powder is talc, and its chemical composition may include: by mass percentage, 50% to 60% SiO2, 10% to 15% K20 and 30% to 40% Al203. Figures 1 to 3 As shown in , the content of montmorillonite in sodium bentonite, the content of kaolinite in kaolin, and the content of talc in talc powder are all ≥90%.

[0040] In this exemplary embodiment, the pressing may include:

[0041] The second mixed material is placed in a mold and pressed into a cylinder with a height of 4.0 cm to 6.0 cm and a diameter of 4.0 cm to 6.0 cm by a hammer press. For example, the second mixed material is pressed into a cylinder with a height of 4.9 to 5.1 cm and a diameter of 5 cm, which is convenient for testing the wet compressive strength. However, the present invention is not limited thereto, and the second mixed material can also be pressed into samples of other shapes.

[0042] In this exemplary embodiment, the wet compressive strength may be 130 kpa to 170 kpa, for example, 140 kpa, 150 kpa, etc.

[0043] In this exemplary embodiment, the quartz sand may be industrial standard sand, and the particle size may be 50-100 mesh or 70-140 mesh.

[0044] In this exemplary embodiment, the particle sizes of the bentonite, kaolin and talc may be 100-200 meshes.

[0045] In this exemplary embodiment, the method may further include the steps of:

[0046] Before mixing bentonite, kaolin and talc, the bentonite, kaolin and talc are dried respectively so that their respective moisture contents are ≤3%.

[0047] Specifically, the method of the present invention using bentonite composite sand casting test comprises the following steps:

[0048] The first step: obtaining a mixture of bentonite, kaolin and talc.

[0049] Dry the bentonite, kaolin and talcum powder, and then mix the three dried powders in a mixer. The drying process can be carried out in a dryer, and the temperature, time and other parameters of the dryer are adjusted so that the moisture content of the dried bentonite, kaolin and talcum powder is ≤3%, such as 1%, 2%, etc., so as to obtain dry powder. Then add the three powders into the mixer and stir and mix them. The stirring time is 20min to 50min. During the mixing and stirring, add an appropriate amount of water to keep the humidity of the mixture at 5% to 10%. Bentonite is the main ingredient in this formula. When the addition amount of bentonite meets 75% or more, the wet compressive strength of the sample can meet the standard.

[0050] Step 2: Get a mixed sample of quartz sand and bentonite composite formula

[0051] The mixed sample of the three materials obtained in the first step is compounded with quartz sand according to the national standard, and then added into the mixer for mixing again. The mixing time is 20min to 50min. During the mixing process, an appropriate amount of water is added to keep the sample humidity of the mixed material at 5% to 10%. Among them, the quartz sand used is standard sand, and the sample particle size is generally 50 to 100 mesh or 70 to 140 mesh.

[0052] Step 3: Press samples that meet the standards

[0053] The sample obtained in the second step is subjected to a compression test. The machine used for compression is a hammer type compression machine. The mixed sample in the previous step is placed in a cylindrical mold, placed on the hammer type compression machine, and swung 3 to 5 times. The mold is removed to take out the sample. Measure the height of the sample and keep it at 5.00 cm ± 0.1 cm.

[0054] Step 4: Obtain samples with wet compressive strength that meets the standards

[0055] The samples obtained in the third step are sent to a press to test their wet compressive strength, and the wet compressive strength samples that meet the standards are kept for later use.

[0056] Step 5: Factory Cast Aluminum Parts

[0057] The samples that meet the standards prepared in the fourth step are sent to the factory for aluminum casting. The mixed samples are placed in the sample tank, and then the burned aluminum liquid is poured into the sample tank. After the aluminum part is formed, the mold is removed and placed in the water tank to cool down. Finally, the aluminum part is taken out after it cools down.

[0058] In order to better understand the above exemplary embodiments of the present invention, they are further described below in conjunction with specific examples.

[0059] Example 1

[0060] (1) 80 parts by weight of bentonite, 10 parts by weight of kaolin and 10 parts by weight of talc are dried separately for 2 to 5 hours, and then the dried samples are added into a blender and stirred to obtain a first mixed material for later use.

[0061] (2) The first mixed material obtained in step (1) is mixed with quartz sand at a ratio of 1:20, put into a blender, and stirred and mixed, and an appropriate amount of water is added to keep the moisture content at 5%, thereby obtaining a second mixed material.

[0062] (3) The second mixed material obtained in step (2) is added into a mold, and pressed into a cylindrical sample with a height of 5.00 cm ± 0.1 cm and a diameter of 5.00 cm ± 0.1 cm using a hammer. The test compression strength thereof is 147 KPa.

[0063] (4) The cylindrical sample obtained in step (3) is cast into an aluminum part. After the casting is completed, the sample is demolded. The demolding effect is good and no sand will stick to the mold. The sample is placed in a water tank for cooling to obtain a casting. The casting has a high gloss and a smooth surface. Example 2

[0064] (1) 75 parts by mass of bentonite, 15 parts by mass of kaolin and 10 parts by mass of talc are dried separately for 2 to 5 hours, and then the dried samples are added into a blender and stirred to obtain a first mixed material for use.

[0065] (2) The first mixed material obtained in step (1) is mixed with quartz sand at a ratio of 1:20, put into a blender, and stirred and mixed, and an appropriate amount of water is added to keep the moisture content at 8%, thereby obtaining a second mixed material.

[0066] (3) The second mixed material obtained in step (2) is added into a mold, and pressed into a cylindrical sample with a height of 5.00 cm ± 0.1 cm and a diameter of 5.00 cm ± 0.1 cm using a hammer. The test compression strength thereof is 145 KPa.

[0067] (4) The cylindrical sample obtained in step (3) is cast into an aluminum part. After the casting is completed, the sample is demolded, and the demolding effect is good, and sand will not stick to the mold. The sample is placed in a water tank for cooling to obtain a casting with high gloss and smooth surface.

[0068] Example 3

[0069] (1) 78 parts by weight of bentonite, 12 parts by weight of kaolin and 10 parts by weight of talc are dried separately for 2 to 5 hours, and then the dried samples are added into a blender and stirred to obtain a first mixed material for later use.

[0070] (2) The first mixed material obtained in step (1) is mixed with quartz sand at a ratio of 1:20, put into a blender, and stirred and mixed, and an appropriate amount of water is added to keep the moisture content at 10%, thereby obtaining a second mixed material.

[0071] (3) The second mixed material obtained in step (2) is added into a mold, and pressed into a cylindrical sample with a height of 5.00 cm ± 0.1 cm and a diameter of 5.00 cm ± 0.1 cm using a hammer. The test compression strength thereof is 157 KPa.

[0072] (4) The cylindrical sample obtained in step (3) is cast into an aluminum part. After the casting is completed, the sample is demolded, and the demolding effect is good, and sand will not stick to the mold. The sample is placed in a water tank for cooling to obtain a casting with high gloss and smooth surface.

[0073] In summary, the beneficial effects of the present invention may include at least one of the following:

[0074] (1) The bentonite composite molding sand of the present invention mainly uses bentonite, kaolin and talc as raw materials to produce an efficient molding sand binder formula, thereby achieving the reusability of the molding sand, realizing resource utilization, and reducing environmental pollution;

[0075] (2) The molding sand sample prepared by the present invention has a higher demolding property, and the prepared sample is less likely to be stuck with sand;

[0076] (3) The raw materials used in the present invention have low ash and sulfur content and are non-toxic and harmless; no toxic or harmful gases are generated during the casting process;

[0077] (4) The materials used in the method of the present invention are cheap and readily available, and the market prices of the samples used are relatively low.

[0078] Although the present invention has been described above in conjunction with exemplary embodiments, it will be apparent to those skilled in the art that various modifications may be made to the above-described embodiments without departing from the spirit and scope of the claims.

Claims

1. A method for a bentonite composite sand casting test, characterized in that: The method comprises the steps of: By mass fraction, 75% to 80% of bentonite, 10% to 15% of kaolin, and 5% to 15% of talc are uniformly mixed to obtain a first mixed material; Before mixing bentonite, kaolin and talc, the bentonite, kaolin and talc are dried respectively so that their respective moisture contents are ≤3%; The kaolin comprises, by mass percentage, 50% to 55% SiO2, 10% to 15% K2O and 30% to 40% Al2O3; the talc comprises, by mass percentage, 50% to 60% SiO2, 10% to 15% K2O and 30% to 40% Al2O3; The first mixed material and quartz sand are mixed in a mass ratio of 1:18-22, and a proper amount of water is added during the mixing process to obtain a second mixed material with a humidity of 5%-10%; Pressing the second mixed material into a sample to obtain a sample of a predetermined shape; Testing the wet compressive strength of the samples, and conducting a casting test on the samples that meet the wet compressive strength requirements; The wet compressive strength is 130 kpa to 170 kpa.

2. The method for sand casting test using bentonite composite formulation according to claim 1, characterized in that: The bentonite comprises, by mass percentage, 60% of SiO2, 20% to 30% of Al2O3, 10% to 15% of Na2O, 1% to 5% of MgO and 5% to 10% of CaO.

3. The method for sand casting test using bentonite composite formulation according to claim 1, characterized in that: The compression sample comprises: The second mixed material is placed in a mold and pressed into a cylinder with a height of 4.0 cm to 6.0 cm and a diameter of 4.0 cm to 6.0 cm using a hammer press.

4. The method for sand casting test using bentonite composite formulation according to claim 1, characterized in that: The quartz sand is industrial standard sand, and the particle size is 50 mesh to 100 mesh or 70 mesh to 140 mesh.

5. The method for sand casting test using bentonite composite formulation according to claim 1, characterized in that: The particle sizes of the bentonite, kaolin and talcum powder are 100-200 meshes.

Citation Information

Patent Citations

  • High crush-resistance moulding sand and preparation method thereof

    CN103042158A

  • High-temperature-resistant molding sand

    CN107414014A